Balance Scorecard Implementation towards new product development and business performance: A systematic review of literature - Zhengxiaoming, Aminaimu; Panigrahi, Shrikant (Universiti Malaysia Pahang, 2018)
Balances Scorecard (BSC) as a strategic performance tool has received closed attention by many organizations worldwide, however, the implementation has been limited. The globalization and economic turbulence have increased the challenges to the executives face and therefore need to find the right tools to overcome the challenges. The current paper focuses on a review of literature on the importance of BSC towards new product development and business performance. The 4th generation balanced scorecard leads the combination of management system and performance measurement that brings up one big strategy maps, and possibly will use widely to satisfy the customer demands. The industry 4.0 will help enlarge the big pictures of new product development based on customer needs. This paper discusses on the current issues and emerging importance of BSC literature and suggests fruitful areas for further research.